ANALISIS SISTEM BAGI HASIL PADA PENDAPATAN MASYARAKAT NELAYAN DI DESA SINGKUANG KECAMATAN MUARA BATANG GADIS KABUPATEN MANDAILING NATAL - Adriana Sari; Nahar Alang Abdul Ghani; Eli Agustami (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
The profit-sharing system is a system in which an agreement or joint bond in the business is agreed upon for the sharing of profits or losses that will be shared between two or more parties. This study aims to determine the cooperation agreement between toke and fishermen in Singkuang Village, Muara Batang Gadis District, Mandailing Natal Regency and to determine the implementation of the profit sharing system between toke and fishermen carried out in Singkuang Village, Muara Batang Gadis District, Mandailing Natal Regency. This type of research is quantitative research. Collecting data in the form of a questionnaire. The data analysis method used is descriptive quantitative. The results of this study indicate that 1. The system of cooperation agreements carried out between toke and fishermen in Bagan Deli Village, Medan Belawan District, is by using a profit-sharing system whose agreement has been carried out for generations, namely by using a method that is only done verbally and trusting each other. one another. 2. The implementation of the profit sharing system carried out by the toke with the fishermen, namely there are 2 types of distribution, the first type of profit sharing is the profit sharing system between the toke and the fisherman whose marine products must be sold with the toke in question and is carried out by means of five divisions, namely the toke gets 1 share and fishermen get 4 shares and that includes deductions from boat rental fees and oil money when going to sea or in percentage terms, which is 80% for fishermen and 20% for toke. While the second type of profit-sharing system is a profit-sharing system by means of three divisions, namely 2 parts for fishermen and 1 part for toke or in terms of the percentage, which is 65% for fishermen and 35% for toke.